Willingness To Pay Petani terhadap Pelaksanaan Asuransi Usaha Tani Padi (AUTP) (Studi Kasus Subak Cepik Desa Tajen Kecamatan Penebel Kabupaten Tabanan) - NI NENGAH SURNING; I GUSTI AGUNG AYU AMBARAWATI; I NYOMAN GEDE USTRIYANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Farmer’s Willingness to Pay to the Implementation of Rice Farming Insurance(Case Study of Subak Cepik Tajen Village, District of Penebel Tabanan Regency) Asuransi Usaha Tani Padi (AUTP) is one of program by Indonesia Government toprotect the farmers if there is a risk happen and causes the farmer loss their resultsduring paddy farming. Subak Cepik is one of subak join AUTP since 2015 and havingthe most claims in Bali Province. The purpose of this research is to find out aboutwillingness to pay by the farmers or we can understanding it as farmer’s ability to paypremiums AUTP and to know the constraints that occurs in the implementation ofAUTP for the Subak Cepik farmers and PT Jasindo. This research is using descriptivequantitative and descriptive qualitative method and used 40 sample of farmers. Thedata analyzed using Contingent Valuation Method (CVM). The result of this researchshows that farmer’s willingness to pay is Rp 30,853/ha/planting season. The amount issmaller than the current premium of Rp 36,000/ha/planting season.. Besides, thisresearch also shows obstacles in the implementation of AUTP for farmers that is fromthe process of socialization AUTP, premium payment process and claims fund that isstill lack for farming needs and constraints from the PT Jasindo including the processof socialization and registration process of AUTP participants. Subak Cepik farmersstill want government subsidies and want to improve the service of AUTP. Result fromthis research suggest there is a need to synergize PT Jasindo and the farmers need forsynergy. Then, the government also expected to set the AUTP premium in accordancewith the capability of farmers.